Macrobenthic Composition of Sea Water Associated with Seagrass in East and West Portions of the Igang Bay, Nueva Valencia, Guimaras - De La Cruz, Mary Jean L.; Flores, June Raymund Peter; Magramo, Melchor M.; Madas, Christy; Terunez, Marlon (JPAIR Multidisciplinary Research, 2010)
The study investigates the macrofauna composition associated with seagrass communities in west and east portions of Igang Bay Nueva Valencia, Guimaras. The study aims to determine the faunal composition of the macrobenthos in east and west Igang Bay seagrass communities and the physical factors like the substrate type, temperature, salinity, and water depth. The study found that West Igang had a relatively higher diversity index (0.608) than East Igang (0.513), while the index of similarity between the two sites was relatively high (0.667). The physico-chemical parameters were observed to be variable between the two sites, with higher salinity recorded in West Igang and variable temperatures. The type of substrates was relatively similar between sites, with occasional rocky bottoms in West Igang. The study highlights the importance of monitoring and understanding the macrofauna composition associated with seagrass communities as an indicator of the environmental health of marine ecosystems.